Social Construction of Unsubsidized Healthy Latrines - Media Sucahya; Ahmad Sihabudin; Dewi Widowati (Future Science, 2023)
Recent data have shown that approximately 5.86% of 275.773 million of the Indonesian population are practicing open defecation. To align with the sustainable development goals (SDGs), efforts are being made to eradicate unhealthy lifestyle behaviors, including open dedication, by 2030. This achievement requires the intervention of both government and non-governmental organizations, as shown by LAZ HARFA in the Banten Province. The organizations successfully motivated impoverished citizens to construct proper sanitation facilities without subsidies. This study aimed to understand social construction of the impoverished community towards unsubsidized healthy latrines program implemented by LAZ HARFA in the Kertaraharja village, Pandeglang Regency, Banten. The analysis was carried out using a qualitative approach, by employing a purposive sampling technique to select informants based on their involvement in healthy latrines program. The total number of informants was 15, consisting of 8, 6, and 4 as key, main, and additional informants, respectively. The results showed that the community firmly believed in achieving unsubsidized healthy latrines program was possible, despite their impoverished conditions. This program was recognized as a step towards adopting a clean and healthy lifestyle. The community shifted the mindset from practicing open defecation to embracing a clean and healthy lifestyle through collaborative efforts, conducting transcheck walks, village mapping, and making commitments to participate in healthy latrines program. Furthermore, social interaction was fostered among the community through the purchase of materials for constructing latrines facilities and toiletries. LAZ HARFA also employed participatory development communication model that focused on provocation and simulation to evoke feelings of shame, disgust, and nausea. The community introduced economic empowerment and environmental quality enhancement programs to accelerate the progress of healthy latrines program.